“Rerukun”: Pemberdayaan Kelompok Muda-Mudi Adhimukti Abyakta Guna Menjaga Stabilitas Masyarakat Plural di Dusun Lemahduwur, Desa Sitirejo, Malang - Annisa Purnadita; Annisa Izzah Dinillah; Achmad Mufti Fauzi; Firman Rahmad Hafidz; Sri Untari (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2024)
Lemahduwur Hamlet in Sitirejo Village, Wagir District, Malang Regency has a community life with a variety of cultural riches and various types of points of view within it. The life of a pluralistic society is threatened by negative urban culture which can affect the lifestyle of the people there, especially among young people. The Adhimukti Abyakta Young People's Group, as a driving force for young people's activity in the socio-cultural field, carries out the hopes of local residents to continue to provide color and maintain stability amidst the life of the plural society there. The purpose of writing this article is as a form of concrete evidence of community service activities that have been carried out by one of the Malang State University community service teams. This research uses a participatory method, which means it places greater emphasis on active participation from the local community, both from the Sitirejo Village government, Lemahduwur Hamlet community leaders and the Adhimukti Abyakta youth group. The concept of service is carried out by collaborating between the service team and the core management of the Adhimukti Abyakta Youth Group to provide encouragement for innovative activities for all members of the Adhimukti Abyakta Youth Group which can be used as a concrete step for the stability of plural society in Lemahduwur Hamlet. All service activities are organized into a program called "Rerukun" which includes organizational management, interactive workshops between youth and community leaders, humanitarian projects in the form of nature studies, and organizing festivals in Lemahduwur Hamlet. It is hoped that this activity will be able to empower the Adhimukti Abyakta Youth Group in terms of internal strengthening of the group, solving problems for local youth and efforts to maintain the stability of plural society in Lemahduwur Hamlet, Sitirejo Village, Malang Regency.